Saposin-like protein 2 has an immunodiagnostic potential for detecting Fasciolosis gigantica - Kueakhai,P. (Academic Press Inc., 2015)
© 2015 Elsevier Inc. Saposin-like protein 2 (SAP-2) plays an important role in the digestive process of Fasciola gigantica (Fg). It is one of the major proteins synthesized by the caecal epithelial cells and released into fluke's excretion-secretion. Therefore, FgSAP-2 is a plausible target for detecting fasciolosis. A polyclonal antibody (PoAb) against recombinant FgSAP-2 was produced by immunizing rabbits with the recombinant protein (rFgSAP-2), and used in sandwich ELISA assay to detect the circulating FgSAP-2 in sera of mice experimentally infected with F. gigantica metacercariae. The assay could detect rFgSAP-2 and the native FgSAP-2 in the excretory-secretory (ES) and whole body (WB) fractions of adult F. gigantica at the concentrations as low as 38 pg/ml, 24 ng/ml, and 102 ng/ml, respectively. As well, the sera from mice experimentally infected with F. gigantica were tested positive by this sandwich ELISA, which exhibited sensitivity, specificity, false positive rate, false negative rate and accuracy at 99.99, 98.67, 1.33, 0.01 and 99.32%, respectively. Therefore, this assay could be used for diagnosis of fasciolosis by F. gigantica.